Підгірцівська група пам’яток Середнього Подніпров’я: стан та перспективи дослідження - Ржевуська, С.С. (Археологія і давня історія України, 2022)
У статті розглянуто історію та історіографію дослідження підгірцівської групи пам’яток VI—IV ст. до н. е. на території Верхнього та Середнього Подніпров’я. Виокремлено етапи за особливостями та рівнем проведення досліджень — від накопичення матеріалів до їх інтерпретації. Наведено дані про актуальний каталог пам’яток, окреслено хронологічні та територіальні межі групи у контексті поселенської структури скіфського часу. Обґрунтовано використання особливих ажурних бронзових (біметалевих) прикрас, а саме дисків та шпильок із навершям у вигляді здвоєних щитків або ж розетти, виконаних у техніці лиття за восковою моделлю, в якості культурних та хронологічних маркерів підгірцівської групи пам’яток. Подальші аналітичні побудови полягатимуть у розробці окреслених питань і реконструкції етнокультурного розвитку на території Середнього Подніпров’я VII—IV ст. до н. е. в цілому. The paper is devoted to the history and historiography of the research of the Pidhirtsi group of sites of the Upper and Middle Dnieper basins of the Scythian Age. The source base includes 131 sites (82 of the Pidhirtsi type and 49 of the Mylohrad culture), which are located within the administrative boundaries of modern Ukraine. Chronological range is defined extending from the middle of 7th to the second quarter of 4th century BC. The territory covers the Middle Dnipro, Desna, Upper Horyn and Southern Buh basins which are the border between the forest-steppe and the mixed forests zones. The majority of the sites were explored during fieldwalking survey with prospect trenches. On the excavated Pidhirtsi settlement special openwork bronze adornments identical to the Pidhirtsi treasure were found. Based on these materials in 1950 V. M. Danylenko singled out the Pidhirtsi group of sites. There are four stages of research of the Pidhirtsi sites — from the accumulation of the materials to the interpretation. The first one (1915—1950s) is associated with the formation of the source base. In the second stage (1950— 1970s) systematic study of the sites of the Upper and Middle Southern Buh and Lower Dnieper basins began. The third stage (1970—1990s) is characterized by attempts to systematize the identified materials. In the fourth stage (since the 1990s), researchers begin focusing on the interpretation of Pidhirtsi type adornments and implement the results for reconstructing the ethnic and cultural situation of the Middle Dnieper region in the Early Iron Age. For a fact, the openwork bronze (bimetallic) adornments are cultural and chronological markers of the Pidhirtsi group of sites. In conclusion, topical issues of future research will be related to technological and morphological aspects of the Pidhirtsi type adornments, the origin, classification and dating.